Uma análise da eficácia jurisdicional para alcançar justiça por meio dos sistemas jurídicos - Andrade Júnior, Carlos Sérgio Dias (2019)
The statement of reasons of the judicial decision is the essence of the judgment. It defines the validity of the decision. However, remain questions about how to check the validity of the statement of reasons: if it would be correct to analyze through its docking in the positive normative system, or rather analyze through the perspective of the effectiveness of the solution presented to the concrete case, even if its statement of reasons is by non-normative factors. The present work intends to answer these questions by the analysis, firstly, of the different legal systems, passing to the analysis of the positivism and the legal realism juridical schools and, ultimately, the influences of these two schools in the construction of the theory of the statement of reasons of the decision in the Brazilian judiciary. The research of the influences of these schools, in a more practical way, intends to answer if a particular mixed legal system to the form the statement of reasons of the decision exists in Brazil, and if this system seek justice or formality in the decision, making such analysis under the point of view of judicial effectiveness and legal reliability.